PlantDRs: A Database of Dispersed Repeats in Plant Genomes Identified by the Iterative Procedure Method - Valentina Rudenko; Eugene Korotkov; Dmitrii Kostenko (Data)
In this work, we searched for and analyzed highly divergent dispersed repeats (DRs) in the genomes of four plants: Arabidopsis thaliana, Capsicum annuum, Daucus carota, and Zea mays. DRs were detected using the iterative procedure method which has shown efficacy in searches for highly divergent repeats in bacteria and algae. The results indicated that the number of DRs in the plant genomes depended on the genome size, whereas the number of repeat families did not. The DRs covered from 36 to 50% of the studied genomes. The shortest repeats were observed in the D. carota genome, but their consensus lengths were similar to those in the other species. Analysis of periodicity in various DR families showed that most periods were 3 bp long. We created a database of the detected DRs, which contains 5,392,216 DRs grouped in 150 families and which can be accessed on the Research Center of Biotechnology RAS server. The server makes it possible to search for repeats based on various criteria and to download the obtained data.